The hush - Hart, John, 1965- (St. Martins Press, 2018)
It's been ten years since the events that changed Johnny Merrimon's life and rocked his hometown to the core. Since then, Johnny has fought to maintain his privacy, but books have been written of his exploits; he has fans, groupies. Living alone in the wilderness beyond town, Johnny's only connection to normal life is his old friend, Jack. They're not boys anymore, but the bonds remain. What they shared. What they lost.